Interrelations of Justice, Rejection, Provocation, and Moral Disgust Sensitivity and Their Links with the Hostile Attribution Bias, Trait Anger, and Aggression - Bondü, Rebecca; Richter, Philipp (Frontiers in Psychology, 2016)
Several personality dispositions with common features capturing sensitivities to negative social cues have recently been introduced into psychological research. To date, however, little is known about their interrelations, their conjoint effects on behavior, or their interplay with other risk factors. We asked N=349 adults from Germany to rate their justice, rejection, moral disgust, and provocation sensitivity, hostile attribution bias, trait anger, and forms and functions of aggression. The sensitivity measures were mostly positively correlated; particularly those with an egoistic focus, such as victim justice, rejection, and provocation sensitivity, hostile attributions and trait anger as well as those with an altruistic focus, such as observer justice, perpetrator justice, and moral disgust sensitivity. The sensitivity measures had independent and differential effects on forms and functions of aggression when considered simultaneously and when controlling for hostile attributions and anger. They could not be integrated into a single factor of interpersonal sensitivity or reduced to other well-known risk factors for aggression. The sensitivity measures, therefore, require consideration in predicting and preventing aggression.